Gadolinium-enhanced MR of chronic dural sinus thrombosis. - Dormont, D; Sag, K; Biondi, A; Wechsler, B; Marsault, C (American Journal of Neuroradiology, 1995)
Gadopentetate dimeglumine-enhanced MR imaging was performed in four patients with chronic dual sinus thrombosis. After injection, intense enhancement of the chronic thrombus was observed in all cases. On three-dimensional time-of-flight MR angiography, performed in one case, the occluded part of the superior sagittal sinus was not distinguishable from a normal sinus because of thrombus enhancement mimicking blood flow. Enhancement of the clot is best explained by organization of the thrombus, which is converted into vascularized connective tissue. It could lead to false-negative results in patients with chronic dural sinus thrombosis studied with contrast-enhanced MR or contrast-enhanced time-of-flight MR angiography techniques.